Immunohistochemical expression of oestrogen and progesterone receptors during experimental acute and chronic murine Schistosomiasis mansoni Expressão imunohistoquímica de receptores para estrogênio e progesterona nas fases aguda e crônica da esquistossomose mansônica experimental em camundongos - Fawzia Ahmed Habib; Mayssa Mohamed Zaki; Amany Ahmed Abd El-Aal; Maha Dia Eldean Safwat; Magda Ahmed El Domiaty (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: The responsibility of Schistosoma mansoni in female infertility is still controversial. This study was conducted to evaluate the effect of acute and chronic schistosomiasis mansoni infection on the endometrium using immunohistochemical analysis of uterine hormone receptor expression. METHODS: Twenty-four nonpregnant swiss albino mice were divided into three groups: control, noninfected; acute; and chronic Schistosoma mansoni infection. Histological sections of uterine specimens were examined by light microscope with an image analyzing system to detect structural histological, estrogen receptor (ER) and progesterone receptor (PR) expression in the endometrium. RESULTS: No secretory phase was detected in the endometrium in acute and chronic Schistosoma infection. Hormone receptor expression (ER and PR) showed statistically significant differences among the groups (p< 0.05), with significant low ER hormone expression in chronic infection, compared to control proliferative, control secretory and acute infection cases, and statistically significant high PR expression in both acute and chronic infection cases compared to the control secretory cases (p< 0.05). CONCLUSIONS: Schistosomiasis mansoni seems to have an important impact on the hormone expression of affected women. Further studies to explore the mechanism of such changes are recommended. INTRODUÇÃO: A responsabilidade do Schistosoma mansoni em esterilidade feminina é ainda controversa. Este estudo é conduzido para avaliar o efeito da esquistossomose mansoni aguda e crônica no endométrio usando análise de imuno-histoquímíca da expressão de receptor hormonal uterina. MÉTODOS: Vinte e quatro camundongos fêmeas albinas suíças não grávidas foram divididas em 3 grupos (controle não-infectado, grupos agudos e crônicos infeccionados com Schistosoma mansoni). As seções histológicas de espécimes uterinos foram examinadas por microscópio leve com imagem, analisando sistema para detectar no endométrio expressões histológicas estruturais, receptor de estrogênio (ER) e receptor de progesterona (PR). RESULTADOS: Nenhuma fase secretora foi detectada no endométrio com infecção aguda e crônica de Schistosoma. A expressão hormonal de receptor (ER e PR) mostrou diferenças estatisticamente significantes entre grupos diferentes (p<0,05) com baixa significativa hormonal de ER com infecção crônica (comparado com controle proliferativo, controle secretório e casos agudos de infecção) e alta expressão de receptor de PR estatisticamente significativa em casos tanto agudos e crônicos de infecção como comparado com os casos de controle secretório (P <0,05). CONCLUSÕES: A esquistossomose mansoni parece ter um maior impacto em expressão hormonal das mulheres afetadas. Mais estudos para explorar o mecanismo de tais mudanças são recomendados.